2021
DOI: 10.1007/s00439-021-02345-5
|View full text |Cite
|
Sign up to set email alerts
|

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype

Abstract: Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…The pathophysiological role of hyperammonemia, argininosuccinate toxicity, 5 and deficiency of arginine and downstream metabolites (i.e., creatine and polyamines) 2 has been proposed to account for the neurological phenotype in ASA. However novel pathophysiological insights have highlighted the role of reversible neuronal nitro‐oxidative stress 6 and central catecholamine deficiency caused by NO deficiency 7,8 . The standard of care in ASA relies on ammonia control using a protein‐restricted diet, ammonia scavengers, and arginine supplementation (which promotes nitrogen waste through the urea cycle), 9,10 with an increasing number of patients treated by liver transplantation 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological role of hyperammonemia, argininosuccinate toxicity, 5 and deficiency of arginine and downstream metabolites (i.e., creatine and polyamines) 2 has been proposed to account for the neurological phenotype in ASA. However novel pathophysiological insights have highlighted the role of reversible neuronal nitro‐oxidative stress 6 and central catecholamine deficiency caused by NO deficiency 7,8 . The standard of care in ASA relies on ammonia control using a protein‐restricted diet, ammonia scavengers, and arginine supplementation (which promotes nitrogen waste through the urea cycle), 9,10 with an increasing number of patients treated by liver transplantation 11 …”
Section: Introductionmentioning
confidence: 99%
“…However novel pathophysiological insights have highlighted the role of reversible neuronal nitro-oxidative stress 6 and central catecholamine deficiency caused by NO deficiency. 7,8 The standard of care in ASA relies on ammonia control using a protein-restricted diet, ammonia scavengers, and arginine supplementation (which promotes nitrogen waste through the urea cycle), 9,10 with an increasing number of patients treated by liver transplantation. 11 Epilepsy is a common comorbidity in ASA, which is thought to affect 40% of patients.…”
mentioning
confidence: 99%
“…In the past decade, researchers have found that ALDH1A1 had vital physiological and pathophysiological functions in many systems, such as the central nervous system, as well as inflammatory and metabolic disorders (5)(6)(7). ALDH1A1 overexpression has been found to play an important role in obesity, diabetes, and other diseases (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the spectrum of clinical severity of the same UCD can be highly variable between individuals 13 , 18 , 19 . Yet, despite a common cerebral toxicity as a result of hyperammonaemia, there are pathophysiological specificities, which remain only partially understood, such as arginase deficiency and dysmyelination 20 , argininosuccinic aciduria and oxidative stress 21 24 , or Lysinuric Protein Intolerance and impaired phagocytosis 25 . Some mouse models fail to recapitulate the human phenotype, such as the hypomorphic Spf ash mouse modelling ornithine transcarbamylase deficiency (OTCD), where a high residual ureagenesis capacity prevents hyperammonaemia, UCDs’ cardinal feature, under standard diet.…”
Section: Introductionmentioning
confidence: 99%